MODERN DEVELOPMENT OF PUBLIC ADMINISTRATION MECHANISMS IN THE FIELD OF FIRE SAFETY IN UKRAINE - Borisov , A. (Theory and Practice of Public Administration, 2020)
The article substantiates that an important goal of public administration in the field of fire safety in Ukraine is to ensure protection of citizens and the national economy from fires, as well as increase the degree of protection against fires, innovative development of organizational and technical measures ensuring fire safety, initiating favorable conditions for the effective implementation of state policy in the field of fire safety. It is proved that today, in the theoretical and methodological achievements of this area, only partially highlighted the characteristics of improving the mechanisms of public administration in the field of fire safety, the current state of the legal framework for their formation, features of their organizational structure, functional powers and tasks of government. bodies for their development, as well as ways to increase their effectiveness in Ukraine.It is noted that one of the main executive state bodies in the field of fire safety in Ukraine is the State Emergency Service, which is responsible for the general provision of fire safety. The Civil Service implements the state policy in the field of civil protection of citizens and regions from emergencies, implements the policy of prevention of such situations and elimination of their consequences, forms directions of fire fighting, implements relations in the field of rescue, man-made and fire safety, emergency -rescue services, etc. The main components of the functioning of the complex mechanism of public administration in the field of fire safety in Ukraine are analyzed. These include economic, informational, regulatory, organizational and political mechanisms that use in the process of functioning of their own tools, methods and techniques to influence fire safety management.